2017
DOI: 10.1016/j.jsxm.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Sexual Function Benefits of Long-Term Testosterone Treatment: Longitudinal Results From the Registry of Hypogonadism in Men (RHYME)

Abstract: Overall, we confirmed the broad and sustained benefits of TRT across major QOL dimensions, including sexual, somatic, and psychological health, which were sustained over 36 months in our treatment cohort. Rosen RC, Wu F, Behre H, et al. Quality of Life and Sexual Function Benefits Effects of Long-Term Testosterone Treatment: Longitudinal Results From the Registry of Hypogonadism in Men (RHYME). J Sex Med 2017;14:1104-1115.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
3
15
1
3
Order By: Relevance
“…Studies have shown that testosterone replacement therapy (TRT) can offer a wide range of benefits that extend beyond sexual health for men with hypogonadism. These include improved: mood; cognition; muscle mass; bone density; red blood cell production, and metabolic control . There is also increasing research demonstrating that all‐cause mortality in men who have a low testosterone level is higher than in those with a normal testosterone level …”
Section: Epidemiology and Diagnosis Of Tdsmentioning
confidence: 99%
“…Studies have shown that testosterone replacement therapy (TRT) can offer a wide range of benefits that extend beyond sexual health for men with hypogonadism. These include improved: mood; cognition; muscle mass; bone density; red blood cell production, and metabolic control . There is also increasing research demonstrating that all‐cause mortality in men who have a low testosterone level is higher than in those with a normal testosterone level …”
Section: Epidemiology and Diagnosis Of Tdsmentioning
confidence: 99%
“…In the case of sexual problems due to hypogonadism and erectile dysfunction, testosterone and phosphodiesterase type 5 inhibitor (PDE5 inhibitors) can improve sexual function [28,[33][34][35]. For treatment or prevention of postmenopausal vaginal atrophy, various options are available, such as hormonal replacement therapy (systemic and topical) [36].…”
Section: Treatment Strategies For Sexual Dysfunctionmentioning
confidence: 99%
“…5. Sexuality: Lower T is associated with lower sexuality, variously measured (Yeap et al 2012;Corona et al 2017;Rizk et al 2017;Rosen et al 2017).…”
Section: Introductionmentioning
confidence: 99%